Предмет: Алгебра,
автор: mostbash
Решительно, пожалуйста! (x-2)^2+48=(2-3x)^2
Ответы
Автор ответа:
0
Решение:
(х-2)^2 +48=(2-3x)^2
x^2 -4x +4 +48=4-12x+9x^2
x^2 -4x +4 +48-4+12x-9x^2=0
-8x^2+8x+48=0 Сократим, разделив каждый член уравнения на (-8)
x^2 -x -6=0
x1,2=(1+-D)/2*1
D=√(1²-4*1*-6)=√(1+24)=√25=5
х1,2=(1+-5)2
х1=(1+5)/2=6/2=3
х1=3
х2=(1-5)2=-4/2=-2
х2=-2
Ответ: (-2; 3)
(х-2)^2 +48=(2-3x)^2
x^2 -4x +4 +48=4-12x+9x^2
x^2 -4x +4 +48-4+12x-9x^2=0
-8x^2+8x+48=0 Сократим, разделив каждый член уравнения на (-8)
x^2 -x -6=0
x1,2=(1+-D)/2*1
D=√(1²-4*1*-6)=√(1+24)=√25=5
х1,2=(1+-5)2
х1=(1+5)/2=6/2=3
х1=3
х2=(1-5)2=-4/2=-2
х2=-2
Ответ: (-2; 3)
Похожие вопросы
Предмет: Биология,
автор: vanyadanilov0708
Предмет: Физика,
автор: sevochkadevochka42
Предмет: Биология,
автор: dunakruckova
Предмет: Математика,
автор: HастенКа